Energy-efficient methane production from macroalgal biomass through chemo disperser liquefaction. (March 2017) - Tamilarasan, K.; Kavitha, S.; Rajesh Banu, J.; Arulazhagan, P.; Yeom, Ick Tae
Graphical abstract: Highlights: Chemo disperser liquefaction boost up disintegration synergistically. This modernistic method induces solubilization at DSE of 3312.6 kJ/kg TS. Kinetic study represents rapid disintegration rate by this incentive process. Chemo disperser liquefaction archived a higher biodegradability (0.14 g COD/g COD). Net profit of about 4 USD/per ton of algae biomass was achieved. Abstract: In this study, an effort has been made to reduce the energy cost of liquefaction by coupling a mechanical disperser with a chemical (sodium tripolyphosphate). In terms of the cost and specific energy demand of liquefaction, the algal biomass disintegrated at 12, 000 rpm for 30 min, and an STPP dosage of about 0.04 g/g COD was chosen as an optimal parameter. Chemo disperser liquefaction (CDL) was found to be energetically and economically sustainable in terms of liquefaction, methane production, and net profit (15%, 0.14 g COD/g COD, and 4 USD/Ton of algal biomass) and preferable to disperser liquefaction (DL) (10%, 0.11 g COD/g COD, and -475 USD/Ton of algal biomass).